Director Characteristics and Firm Performance - Pascal Gantenbein; Christophe Volonté (University of Basel, Center of Business and Economics (WWZ), 2011)
The traditional methodology examining optimal boards relates a simple board variable (e.g., independence or board demography) to firm performance, however, ig- noring other board characteristics. This paper investigates how the education and business experience of directors affect firm performance. The sample consists of 1,574 directorships from 224 listed firms in Switzerland. Using OLS and including control variables, the results show that graduates of minor Swiss universities are negatively related to Tobin's Q, and industrial knowledge and Tobin's Q are nega- tively correlated if the firm has more divisions. In addition, director fixed effects (or unobserved characteristics) are significant, but improve the explanatory power of the models only by 5 percent.
Keywords: G30; G34; G38; 330; Corporate governance: Board of directors; Director characteristics; Education and business experience; Corporate Governance; Board of Directors; Qualifikation; Unternehmenswachstum; Tobins Q; Schweiz